2014
DOI: 10.1016/j.pharep.2013.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between plasma concentration of metoprolol and CYP2D6 genotype in patients with ischemic heart disease

Abstract: The currently used b-blockers differ in their selectivity for b 1 -and b 2 -adrenergic receptors, lipophilicity and route of elimination. Metoprolol is one of the most commonly used b-blockers in the treatment of ischemic heart disease. Metoprolol is a lipophilic b 1 -selective blocker. This drug is well absorbed from the gastrointestinal tract and undergoes extensive distribution in body tissues; it also passes through the blood-brain barrier. The highest plasma concentration value of metoprolol is reached ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We observed that cytochrome p450 genes and transporters were differentially expressed in iHeps, fetal hepatocytes and HepG2. This is not surprising given the variation in CYP gene induction kinetics and CYP polymorphisms (pharmacogenetics) in individuals of different genetic backgrounds that have been shown to affect drug metabolism and clearance [45,46,63,64]. Establishing a repertoire of well-characterized iPSC lines from individuals of diverse genetic backgrounds and/or collecting iPSC lines with genetically engineered CYP genes can be useful for the treatment of the wide range of liver diseases due to drug overdoses or altered CYP metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that cytochrome p450 genes and transporters were differentially expressed in iHeps, fetal hepatocytes and HepG2. This is not surprising given the variation in CYP gene induction kinetics and CYP polymorphisms (pharmacogenetics) in individuals of different genetic backgrounds that have been shown to affect drug metabolism and clearance [45,46,63,64]. Establishing a repertoire of well-characterized iPSC lines from individuals of diverse genetic backgrounds and/or collecting iPSC lines with genetically engineered CYP genes can be useful for the treatment of the wide range of liver diseases due to drug overdoses or altered CYP metabolic activity.…”
Section: Discussionmentioning
confidence: 99%